2013
DOI: 10.1128/jvi.03494-12
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G Impairs the Multimerization of the HIV-1 Vif Protein in Living Cells

Abstract: Gag , Vif is largely relocated to the cell membrane, where Vif oligomerization also occurs. Interestingly, wild-type A3G strongly interferes with Vif multimerization, contrary to an A3G mutant that does not bind to Vif. These findings confirm that Vif oligomerization occurs in living cells partly through its C-terminal motif and suggest that A3G may target and perturb the Vif oligomerization state to limit its functions in the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 81 publications
(132 reference statements)
2
30
0
3
Order By: Relevance
“…The oligomerization of HIV-1 Vif into high-molecular-mass complexes is crucial for inducing Vif folding and binding onto HIV-1 genomic RNA, thereby enhancing HIV-1 Vif packaging into viral particles. A3G was found to be a regulator that strongly interferes with HIV-1 Vif multimerization to limit Vif function (55). It has also been proposed that CBF-␤ inhibits HIV-1 Vif oligomerization to promote the assembly of a well-ordered Vif-E3 complex (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oligomerization of HIV-1 Vif into high-molecular-mass complexes is crucial for inducing Vif folding and binding onto HIV-1 genomic RNA, thereby enhancing HIV-1 Vif packaging into viral particles. A3G was found to be a regulator that strongly interferes with HIV-1 Vif multimerization to limit Vif function (55). It has also been proposed that CBF-␤ inhibits HIV-1 Vif oligomerization to promote the assembly of a well-ordered Vif-E3 complex (36).…”
Section: Discussionmentioning
confidence: 99%
“…3B) or other non-primate lentiviral Vifs (data not shown). Previous studies have shown that HIV-1 Vif forms oligomers or multimers in cells (53)(54)(55). The oligomerization of HIV-1 Vif into high-molecular-mass complexes is crucial for inducing Vif folding and binding onto HIV-1 genomic RNA, thereby enhancing HIV-1 Vif packaging into viral particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…164 motif critical for Vif oligomerization 33,34 and its interaction with the cellular kinase Hck 34,35 ; and (3) a domain (residues 172-192) important for binding with Pr55…”
Section: Pplpmentioning
confidence: 99%
“…18,34 We thus focused our analysis on the characterization of Vif domains regarding their capacity to self-assemble, their secondary structure, together with their RNA binding and chaperone activities.…”
Section: Rational Design Of Hiv-1 Vif Domains and Their Purificationmentioning
confidence: 99%